Human Tissue Kallikreins-Related Peptidases Are Targets for the Treatment of Skin Desquamation Diseases - Zani, Marcelo B.; Sant'Ana, Aquiles M.; Tognato, Rafael C.; Chagas, Jair R.; Puzer, Luciano (Frontiers in Medicine, 2022)
Human tissue Kallikrein-related peptidases (hKLKs) are serine proteases distributed in several tissues and involved in several biological processes. In skin, they are responsible for skin desquamation in Stratum Corneum (SC) of the epidermis, specially hKLK5, hKLK7, hKLK6, hKLK8 and hKLK14. In SC, hKLKs cleave proteins of corneodesmosomes, an important structure responsible to maintain corneocytes attached. As part of skin desquamation, hKLKs are also involved in skin diseases with abnormal desquamation and inflammation, such as Atopic Dermatitis (AD), psoriasis, and the rare disease Netherton Syndrome (NS). Many studies point to hKLKs overexpression or overactive in skin diseases, and they are also part of the natural skin inflammation process, through PAR2 cleavage pathway. Therefore, the control of hKLKs activity may offer successful treatments for skin diseases, improving the quality of life in patients. Diseases like AD, Psoriasis and NS have impact on social life, causing pain, itchy and mental disorders. In this review, we address the molecular mechanisms of skin desquamation, emphasizing the roles of human tissue Kallikrein-related peptidases, and the promising therapies targeting the inhibition of hKLKs.